The synthesis, characterization, and theoretical analysis of (NH4)3PbCl5. (15th January 2021) - Zhu, Liang; Jin, Wenqi; Yang, Zhihua; Yang, Yun; Pan, Shilie
Abstract : (NH4 )3 PbCl5 features a 3D structure with a short UV cutoff edge of 256 nm and simulated birefringence of about 0.050 at 1064 nm. Abstract : A new compound, namely (NH4 )3 PbCl5, has been synthesized via a low-temperature molten salt method in a closed system. It crystallizes in the orthorhombic Pnma (No. 62) space group. The crystal structure of (NH4 )3 PbCl5 features a distinct three-dimensional network constructed via hydrogen bonds that exist between ammonium and chloride anions. The UV-Vis-NIR diffuse reflectance spectrum displays a short UV cutoff edge at about 256 nm. Besides, the thermal behavior (TG and DSC) was also analyzed. To better understand the structure–property relationships of (NH4 )3 PbCl5, theoretical calculations based on density functional theory were also performed. The result shows that the birefringence is expected to be about 0.050 at 1064 nm, and the bandgap is about 4.45 eV, which is consistent with the experimental result.